2021
DOI: 10.1038/s41598-021-84002-5
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by arbuscular mycorrhizal fungi improves salinity tolerance of eucalyptus (Eucalyptus camaldulensis) seedlings

Abstract: Soil salinity affects soil quality and reduces plant performance. Arbuscular mycorrhizal fungi (AMF) can enhance the tolerance of plants under salinity stress. Cultivation of eucalyptus (Eucalyptus camaldulensis), which exhibits high water use efficiency, is possible in saline areas to produce raw materials for the pulp industry. We determined the effects of arbuscular mycorrhizal fungi (AMF) on the growth and survival of eucalyptus seedlings under saline conditions. Three different clones of eucalyptus seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 48 publications
3
28
0
3
Order By: Relevance
“…A mixture of salt-tolerant AMF, viz. Glomus sp., Gigaspora albida, and Gigaspora decipiens also conferred an enhanced degree of salt tolerance in Eucalyptus seedlings by increasing chlorophyll content and K + /Na + ratio (Klinsukon et al, 2021) plant growth and glycyrrhizin production by maintaining ion homeostasis and enhanced proline biosynthesis. Similar growth promotion activities of AMF genera Claroideoglomus claroideum and Glomus mosseae under salinity stress condition were also observed (Santander et al, 2019;Shi-chu et al, 2019).…”
Section: Funneliformis Mosseae and Diversispora Versiformis To Salt-stressedmentioning
confidence: 98%
See 1 more Smart Citation
“…A mixture of salt-tolerant AMF, viz. Glomus sp., Gigaspora albida, and Gigaspora decipiens also conferred an enhanced degree of salt tolerance in Eucalyptus seedlings by increasing chlorophyll content and K + /Na + ratio (Klinsukon et al, 2021) plant growth and glycyrrhizin production by maintaining ion homeostasis and enhanced proline biosynthesis. Similar growth promotion activities of AMF genera Claroideoglomus claroideum and Glomus mosseae under salinity stress condition were also observed (Santander et al, 2019;Shi-chu et al, 2019).…”
Section: Funneliformis Mosseae and Diversispora Versiformis To Salt-stressedmentioning
confidence: 98%
“…A mixture of salt‐tolerant AMF, viz. Glomus sp., Gigaspora albida , and Gigaspora decipiens also conferred an enhanced degree of salt tolerance in Eucalyptus seedlings by increasing chlorophyll content and K + /Na + ratio (Klinsukon et al, 2021). According to Amanifar et al (2019), amelioration of salinity stress in Glycyrrhiza glabra was conferred by F. mosseae colonization, which in turn, helped to sustain plant growth and glycyrrhizin production by maintaining ion homeostasis and enhanced proline biosynthesis.…”
Section: Salt‐tolerant Microorganisms: Supporting Plant Performance Under Salinity Stressmentioning
confidence: 99%
“…The addition of Plant Growth Promoting Microorganisms (PGPMs) in nutrient solutions, in float systems, could be beneficial for cannabis seedlings. Recently, studies indicated the positive impact of PGPMs on seedlings of various plant species [29][30][31][32]. PGPMs improve plant nutrition and affect the release of biologically active substances such as phytohormones, vitamins, and enzymes [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…AMF, biotrophic endophytic microorganisms belonging to the phylum Glomeromycota, are a group of fungi that form symbiotic associations within plant roots [13]. Similar to EPF, AMF can help host plants to increase growth and productivity by enhancing the uptake of water and mineral nutrients, improving the soil quality, enhancing stress tolerance, and protecting against plant pathogens [14,15]. However, the distinct feature of the AMF that distinguishes them from EPF is their ability to colonize the belowground parts of plants, which was restricted to plant roots, while AMF fungi only colonized the roots.…”
Section: Introductionmentioning
confidence: 99%